To Tweet or Not to Tweet: An Investigative Analysis of the Government of Canada's Social Media Practices - David, Renée S. (Université d'Ottawa / University of Ottawa, 2014)
The concept of social media is top of mind for Canadians today. Decision makers, such as the Canadian government, try to identify ways in which they can benefit from tools such as Twitter. This thesis is an investigative analysis that studies how the Canadian government currently uses social media networks. Based on the conceptual framework of Rogers’ diffusion of innovations (2003) and Qualman’s socialnomics theory (2013), the study aims to define how members of the Parliamentary Press Gallery use the Government of Canada tweets. Through a series of interviews with members of the press and government communications executives, a themed analysis was conducted to demonstrate how Twitter is being used and if a dialogue exists between federal institutions and reporters. The research unveiled that the Government of Canada uses social media as a one-to-many broadcasting channel, not actively engaging in online dialogue with members of the press. Conversely, journalists use Twitter as a wire service to obtain instant information, and to gain insight from the consumers. However, they are not interested in conversing with the public service on social media as they want to protect the exclusivity of their story, and they criticize the anonymity of the government corporate accounts as having an impact on its credibility.
Keywords: Government of Canada; Journalists; Twitter; Social media; Conversation; Public sector communications